Picturebooks in foreign language classroom - Martincová, Kristýna (Univerzita Pardubice, 2008)
This thesis is concerned with the art form of picturebook and its potential in English language teaching. In its initial part it presents a theoretical overview of both the genre of picturebook and its potential role when used as a teaching aid in young learners’ foreign-language classroom. The research part is then anchored in a set of picturebook-centred teaching sequences devised and carried out by the author in several elementary ESL classrooms, and consequently analysed and evaluated as regards their actual potential and efficiency when applied into language instruction.
Obrázkové knihy ve vyučování cizích jazyků
Keywords: picturebooks; foreign language teaching; young learners; obrázkové knihy; výuka cizích jazyků; žáci mladšího školního věku